Variability of Burnout and Stress Measures in Pediatric Residents: An Exploratory Single-Center Study From the Pediatric Resident Burnout-Resilience Study Consortium - Suzanne Reed MD; Kathi J. Kemper MD, MPH; Alan Schwartz PhD; Maneesh Batra MD; Betty B. Staples MD; Janet R. Serwint MD; Hilary McClafferty MD; Charles J. Schubert MD; Paria M. Wilson MD, MEd; Alex Rakowsky MD; Margaret Chase MD; John D. Mahan MD (SAGE Publishing, 2018)
Residency is a high-risk period for physician burnout. We aimed to determine the short-term stability of factors associated with burnout, application of these data to previous conceptual models, and the relationship of these factors over 3 months. Physician wellness questionnaire results were analyzed at 2 time points 3 months apart. Associations among variables within and across time points were analyzed. Logistic regression was used to predict burnout and compassionate care. A total of 74% of residents completed surveys. Over 3 months, burnout ( P = .005) and empathy ( P = .04) worsened. The most significant cross-sectional relationship was between stress and emotional exhaustion (time 1 r = 0.61, time 2 r = 0.68). Resilience was predictive of increased compassionate care and decreased burnout ( P < .05). Mindfulness was predictive of decreased burnout ( P < .05). Mitigating stress and fostering mindfulness and resilience longitudinally may be key areas of focus for improved wellness in pediatric residents. Larger studies are needed to better develop targeted wellness interventions.